Precoded Cluster Hopping for Multibeam GEO Satellite Communication Systems - Lagunas, Eva; Kibria, Mirza Golam; Al-Hraishawi, Hayder; Maturo, Nicola; Chatzinotas, Symeon (Frontiers in Signal Processing, 2021)
Beam-Hopping (BH) and precoding are two trending technologies for high throughput satellite (HTS) systems. While BH enables the flexible adaptation of the offered capacity to the heterogeneous demand, precoding aims at boosting the spectral efficiency. In this paper, we consider a HTS system that employs BH in conjunction with precoding in an attempt to bring the benefits of both in one. In particular, we propose the concept of Cluster-Hopping (CH), where a set of adjacent beams are simultaneously illuminated with the same frequency resource. On this line, we propose an efficient time-space illumination pattern design, where we determine the set of clusters that shall be illuminated simultaneously at each hopping event along with the dwelling time. The CH time-space illumination pattern design formulation is shown to be theoretically intractable due to the combinatorial nature of the problem and the impact of the actual illumination design on the resulting interference. For this, we make some design decisions on the beam-cluster design that open the door to a less complex, still well-performing solution. Supporting results based on numerical simulations are provided which validate the effectiveness of the proposed CH concept and time-space illumination pattern design with respect to benchmark schemes. This work was supported by Fonds National de la Recherche Luxembourg, Grant Number C19_IS_13696663